Conductus as Analgesic - Gillingham, Bryan (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1994)
One of the difficulties in creating an adequate picture of the contextual situation for music, other than that clearly associated with the liturgy, in the Middle Ages, is the paucity of accounts describing performance circumstances. We know little about the social milieu and purposes attending genres marginal to the liturgy such as the conductus and thirteenth-century motet. A manuscript which seems to redress this problem, albeit for one very specific instance, is Vat. lat. 2854 in the Vatican library in Rome.This manuscript is unusual in that it contains not only music but a detailed account of why the music was written. The author, Bonaiutus de Casentino, active in the circle of Pope Boniface VIII, prepared the manuscript in the last decade of the thirteenth century at Rome. The document includes various poems, sacred and secular, as well as two Latin songs written in late Franconian notation. One of the pieces is a two-voice conductus (Hec medela corporalis) which was written, according to the account of Bonaiutus himself, in order to cure the maladies of an ailing pontif. The pontifical complaints seemed to be both psychological and intestinal in nature. It was the hope of Bonaiutus not only to provoke laughter (always a curative), but also to cleanse the papal bowels through his composition. Although one cannot generalize on the basis of this single incident, it does yield a fascinating glimpse into a possible venue for the conductus.